Production of Hydrogen-Rich Syngas from Dimethyl Ether by Using a Microwave Steam Plasma - Uhm, Han S.; Choi, Chang H.; Lee, Joo Y.; Kim, Dong J.; Woo, Sang G.; Woo, Minwoo; Lee, Dong C. (Journal of the Korean Physical Society, 2019)
Dimethyl ether (DME) is disintegrated by a microwave steam-plasma raising the gas temperature in a reaction chamber of 100 liters in a swirl-type gasifier. With additional heating of DME by partial oxidation, the gasifier temperature reaches 1250 °C. The initial breakdown species of DME molecules are hydrogen, carbon monoxide and methane, which eventually disintegrate to CO and H2 by steam modification at temperatures higher than 1200 °C. The relative concentrations of hydrogen, carbon monoxide and carbon dioxide produced solely from DME modification by steam were 67.5 percent, 30.3 percent and 2.2 percent, respectively, achieving a conversion rate of 88 percent at a temperature of 1058 °C. The total energy efficiency of the present experiment was 81 percent.
Keywords: Dimethyl Ether; Gasification; Microwave torch; Steam plasma